2022
DOI: 10.1038/s41598-022-18899-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact on dental students and professionals in a Lima population during COVID-19s wave: a study with predictive models

Abstract: Peru was the country with the highest COVID-19 case fatality rate worldwide during second wave of infection, with dentists and pre-professional students being susceptible to infection due to clinical procedures they perform. This situation could have generated some kind of psychological disorder within this group. Therefore, the present study aimed to assess how COVID-19 pandemic affected this population group during second wave, in relation to depression, anxiety and stress. This observational and cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…For this reason, some did not agree to participate. 23,46 Despite this, it was possible to complete the minimum sample requirement with stratified probability sampling. Likewise, the decision to carry out this study in a private university with one campus in the capital and another in the province was due to the control of the variable "curricular plan" since the dental schools in Peru do not have the same curricular design.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, some did not agree to participate. 23,46 Despite this, it was possible to complete the minimum sample requirement with stratified probability sampling. Likewise, the decision to carry out this study in a private university with one campus in the capital and another in the province was due to the control of the variable "curricular plan" since the dental schools in Peru do not have the same curricular design.…”
Section: Discussionmentioning
confidence: 99%
“…The independent variables were sex, 14 , 16–18 monthly family income, 20 computer use 21 and age group. 4 , 22 The possible confounding variables were marital status, 2 , 23 academic year, 15 , 17 , 24 area of residence, 17 , 25 place of origin 22 , 26 , 27 and occupation. 28 …”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic, unlike any public health challenge, had the capacity to disrupt the delivery of many services including educational training. 1 , 2 The Peruvian government through Supreme Decree No. 044–2020-PCM extended by Supreme Decrees No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological distress in healthcare is common and may include symptoms of burnout, depression, anxiety, rumination, and perceived stress (9)(10)(11). In this context, in recent studies, it has been reported that students, interns, and dental professionals were more likely to develop mood disorders (12)(13)(14), for example, Mekhemar et al (15) reported higher levels of anxiety, stress, and depression in female dentists aged 50 and 59 years old, with immunodeficiency or with a chronic disease and in those who considered the COVID-19 pandemic as a financial risk. In addition, several sociodemographic factors have been reported to be associated with psychological distress in the context of the pandemic and confinement, such as age, gender, marital status, economic income, and cohabitation with vulnerable people, among others (2,16,17).…”
Section: Introductionmentioning
confidence: 99%